2016
DOI: 10.1038/ncomms11133
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous dynamics of intruders in a crowded environment of mobile obstacles

Abstract: Many natural and industrial processes rely on constrained transport, such as proteins moving through cells, particles confined in nanocomposite materials or gels, individuals in highly dense collectives and vehicular traffic conditions. These are examples of motion through crowded environments, in which the host matrix may retain some glass-like dynamics. Here we investigate constrained transport in a colloidal model system, in which dilute small spheres move in a slowly rearranging, glassy matrix of large sph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
137
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(151 citation statements)
references
References 48 publications
13
137
1
Order By: Relevance
“…As compared to micelles formed in 95% water, a six order of magnitude decrease in the diffusion coefficient of the micelles is observed when the micelles are present in 20% water, the rest being glucose, urea and surfactant. The evolution of the micelles' correlation function with a decrease in water concentration is analogous to that observed in colloids under jammed state 25,26 . In particular, the correlation function changes from a single exponential to a double exponential function as is observed in the case of arrested macromolecules in a crowded environment 27 .…”
Section: Resultssupporting
confidence: 60%
“…As compared to micelles formed in 95% water, a six order of magnitude decrease in the diffusion coefficient of the micelles is observed when the micelles are present in 20% water, the rest being glucose, urea and surfactant. The evolution of the micelles' correlation function with a decrease in water concentration is analogous to that observed in colloids under jammed state 25,26 . In particular, the correlation function changes from a single exponential to a double exponential function as is observed in the case of arrested macromolecules in a crowded environment 27 .…”
Section: Resultssupporting
confidence: 60%
“…These data are treated via an image processing algorithm [22] or equivalent versions of it [23] that combines image differences and spatial Fourier transformations to obtain as a result the intermediate scattering function f (q,t) that is typically probed in DLS experiments as a function of the scattering wave vector q and time t [24]. Since its introduction, DDM has been profitably used and also extended by several groups [25][26][27][28][29][30][31][32][33][34] for a variety of applications [35]. In particular, DDM has been recently proven to be an effective tool to measure also the rotational dynamics of anisotropic colloidal particles in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the ISF can also be obtained from advanced image correlation spectroscopy such as dynamic differential microscopy (DDM) [36,68,69], a method that is also suited to resolve the motion of active particles [70,71]. Here we focus again on tracer particles that are located on the infinite cluster only and modify the definition of the ISF accordingly to…”
Section: Space-resolved Transportmentioning
confidence: 99%
“…For example, for the alkali silica melts [26][27][28][29] the preferential diffusion pathways for the alkali ions emerge as a quasi-arrested defect structure of a tetrahedral network. Similarly, for size-disparate soft [31] or hard spheres [36] the interaction between the particles leads to strong short-range correlations which modify locally the structure of the pores. Nevertheless fingerprints of the anomalous dynamics as predicted for the Lorentz models are clearly found in all these systems.…”
Section: Quenched Host Structuresmentioning
confidence: 99%
See 1 more Smart Citation